Smart card research and advanced applications : 14th International Conference, CARDIS 2015, Bochum, Germany, November 4-6, 2015 revised selected papers /: 14th International Conference, CARDIS 2015, Bochum, Germany, November 4-6, 2015 revised selected papers. (2016) - Unknown
No abstract available